Black liquor gasification : burner characteristics and syngas cooling - Risberg, Mikael (Luleå tekniska universitet, Energivetenskap, 2011)
Black liquor gasification at high temperature is a promising alternative to the conventional recovery boiler process used in chemical pulp mills today. Compared to a conventional recovery boiler a black liquor gasifier can increase the total energy efficiency of a chemical pulp mill and produce a synthesis gas that can be used for production of motor fuel. In Piteå, a 3 MW or 20 tons per day entrained flow pressurized black liquor gasification development plant has been constructed by Chemrec at Energy Technology Center. The plant has been run more than 12 000 h since 2005. One of the key parts in the gasification process is the spray burner nozzle where the black liquor is disintegrated into the hot gasifier as a spray of fine droplets. In this thesis the spray burner nozzle as characterized with high speed photography in order to visualize the atomization process of black liquor. The results showed that black liquor forms non-spherical and stretched ligaments and droplets with the considered nozzle. Comparison of the results with atomization of a syrup/water mixture showed that the results were qualitatively very similar which means that a syrup/water mixture can be used instead of black liquor for burner optimization experiments. This is a considerable experimental simplification. Also spatially resolved measurements of the gas composition in the development plant with a water cooled quench probe have been performed. From the gas composition measurement and the spray visualization it has been showed that the preheating of black liquor has a significant influence on the gas composition. Another important part in the gasification plant is the counter-current condenser where the gas is cooled and the water content in the gas is condensed away in vertical tubes that are cooled on the outside by a counter-current flow of water or steam. In this thesis a computational fluid dynamics model of the counter-current condenser have been developed. The model consists of a two-phase fluid model on the tube-side of the ...